De Finnis cornutis - Pekkanen, Tuomo (Nordlit, 2014)
Horned Finns. The ‘cornuti Finni’ mentioned in the Historia Norwegiae have not found their explanation, because the Latin word cornu, from which the adjective is derived, has been understood in the strict sense of ‘horn on the head’. The Latin word, however, also means ‘hoof’ of horses or ‘cloven hoof’ of cows and goats, even of the mythologic Faunus and Pan. In December 1913 Kai Donner saw in Dudinka Avam-Samojeds, who because of their cylindrically shaped reindeer winter boots, the front of which was hoof-shaped, were called ‘hoofed men’ (in Finnish ‘kaviolliset miehet’). In the extracts of Aristeas of Proconnesus, who as early as about 625 B.C travelled in North-Eastern Asia, the Aigipodes, men with goats feet, are mentioned as inhabitants of Northern Siberia. In the first century A.D., Pomponius Mela knows Hippopodes, men with horse’s feet, in the Northmost Sarmatia. The three names, cornuti Finni, Aigipodes and Hippopodes find their explanation in the reindeer boots, necessary in the arctic climate. Recent photographs of the Ngasani and Nenets Samojed show that this kind of boots are still used. The fact that some arctic peoples have since ancient times got their nickname from their boots, which made them look like hoofed animals, makes it necessary to reconsider the origin of the names Lapp and Finn, the etymology of which is unclear. As the Swedish lapp, earlier form of modern labb, is of Indogermanic origin and has in several languages the meaning of the foot of a quadruped animal, it seems that the name Lapp, considered as abusive by the Sami, belongs to the arctic names given to people who because of their boots looked like men with goat’s or horse’s feet and were called, as Donner heard it, ‘hoofed men’. It remains an open question whether the ethnonym Fenni / Finni may be of similar origin.
Keywords: Cornua pedum; calceamenta Samoiedorum; Aigipodes; Hippopodes; etymologia nominis Lappi